Flaubert libre lecteur. À propos de l’Abrégé du catéchisme de persévérance de l’abbé Gaume - Stéphanie Dord-Crouslé (Flaubert: Revue Critique et Génétique)
By analyzing a precise example, this article focuses on the way Flaubert deals with his documentary readings. What are the principles that guide his choices? Are the notes he takes accurate? What happens to them once they are inserted into fiction? Preserved in the files of the public library in Rouen (ms g 226 (6) f° 227 to 229), the notes that the novelist took from the abridged version of a catechism by the abbé Gaume are particularly revealing: their analysis brings to light various mechanisms at work in his practice of primary documentation as well as in the secondary writing process of the novel (in fact here chapter IX of Bouvard and Pécuchet). As it appears, it is not always where a work is most explicitly quoted that one can find the strongest concentration of documentary references. The integral « diplomatic » transcriptions of the analyzed manuscripts are included.